Seismic Site Response Characterisation of Sungai Serut Sub-district, Bengkulu City, Using the Horizontal to Vertical Spectral Ratio (HVSR) Method - Rendoza; Muchammad Farid; Refrizon Refrizon; Debi Hardiansa; Andre Rahmat Al Ansory; Hana Raihana (Universitas Andalas, 2026)
Bengkulu City, located on the west coast of Sumatra, is highly susceptible to seismic hazards due to active tectonic settings. This study investigates subsurface characteristics, ground amplification, and the seismic vulnerability index (Kg) in Sungai Serut Village using the Horizontal to Vertical Spectral Ratio (HVSR) method based on microtremor measurements. The results indicate that the dominant frequency (f₀) ranges from 1.00 to 6.87 Hz, reflecting variations in sediment stiffness and near surface geological conditions. Based on the dominant frequency distribution, the subsurface materials are predominantly classified as type II soil, which generally corresponds to medium-density sedimentary deposits. The spectral amplification factor (A₀) varies between 1.64 and 5.88, indicating moderate to high amplification levels. The seismic vulnerability index (Kg) ranges from 0.51 to 20.49, with the highest values observed at measurement points 20 and 21, suggesting greater susceptibility to strong ground motion. These findings provide important insights for seismic hazard assessment and support earthquake-resilient spatial planning and infrastructure development in Bengkulu City.